2016
DOI: 10.1002/smll.201601505
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptically Active Plasmonic Nanoparticles Having Hidden Helicity and Reversible Aqueous Solvent Effect on Chiroptical Activity

Abstract: The geometrical prerequisite for forming a helix is P (helical pitch) > d (wire diameter). Limited by the current development of nanofabrication techniques, it is difficult to minimize d and consequently P to the sub-10 nm molecule-comparable scale, preventing the study of chiral plasmonics at dimensions approaching the physical limit. Herein, glancing angle deposition is operated at substrate temperature of 0 °C and high speed of substrate rotation to generate silver nanoparticles (AgNPs) with nominal P < d. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 45 publications
0
58
1
Order By: Relevance
“…The CD spectrum of the chiral AlNPs flips around the zero‐CD axis while the hidden handedness is switched, illuminating that the AlNPs are chiroptically active, intrinsically attributed to the hidden helicity. It was reported that P plays an essential role in determining the chiroptical activity of the plasmonic chiral NPs . The chiral AlNPs exhibit a narrow distribution of P (less than 6.5%, Table S1, Supporting Information), so as to have the well‐defined chiroptical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD spectrum of the chiral AlNPs flips around the zero‐CD axis while the hidden handedness is switched, illuminating that the AlNPs are chiroptically active, intrinsically attributed to the hidden helicity. It was reported that P plays an essential role in determining the chiroptical activity of the plasmonic chiral NPs . The chiral AlNPs exhibit a narrow distribution of P (less than 6.5%, Table S1, Supporting Information), so as to have the well‐defined chiroptical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Cu nanohelices have a chiroptical redshift of the longitudinal mode from 575 to 750 nm with an increase of P from 20 to 100 nm . Ag nanohelices exhibit a pair of bisignate CD peaks located at 370 nm and in the visible region, ascribed to the transverse and longitudinal LSPR modes, respectively . The elongation of Ag nanohelices can barely shift the transverse CD mode, but cause the longitudinal CD mode to have a marked redshift …”
Section: Introductionmentioning
confidence: 99%
“…Template‐assisted electrosynthesis, focused electron beam‐induced deposition and colloidal nanohole lithograph unavoidably involve a set of pre/after‐NH‐fabrication processes. As a result, it can be derived from the comparison that the GLAD technique, without the deposition on a pre‐patterned substrate, provides a one‐step deposition of metallic NHs over a large area and flexible engineering of material and helical structures . The GLAD technique tends to outweigh the other NH‐fabrication approaches, for studying the helicity‐dependent optical/magnetic/magnetochiral properties of plasmonic NHs and developing novel chiroptical devices.…”
Section: Fabrication Of Metallic Nanohelicesmentioning
confidence: 99%
“…Another approach is to monitor CD of an array of metallic NHs vertically protruding on a transparent substrate (e.g., sapphire), exposed to an incidence of CPL along the direction of the substrate normal. The substrate is continuously rotated at an appropriate rate during monitoring a CD spectrum, to eliminate linear anisotropy resulting from structural alignment ascribed to the vertical protrusion of metallic NHs on the substrate …”
Section: Fundamental Properties Of Metallic Nhsmentioning
confidence: 99%
“…[14][15][16][17][18] In metal nanoparticles, localized surface plasmon resonances (coherent oscillations of the free electrons at the surface) can greatly enhance the light-matter interaction and, by extension, the chiroptical interactions. [19][20][21][22] In general, chiroptical interactions can be enhanced by increasing the chirality parameter of the nanostructures [23,24] or of light (optical chirality). [25] Most investigations have been performed on structures with subwavelength dimensions, chiefly because this enables their theoretical treatment within an effective medium approximation.…”
mentioning
confidence: 99%